Dual Modal Imaging-Guided Drug Delivery System for Combined Chemo-Photothermal Melanoma Therapy - Zhang D (Dove Medical Press, 2021)
Dong Zhang,1– 3,* Weifen Zhang,1,2,* Xinghan Wu,1 Qian Li,1,2 Zhiyi Mu,1,2 Fengshuo Sun,1,2 Mogen Zhang,1 Guoyan Liu,3 Linlin Hu1,2 1Shandong Engineering Research Center for Smart Materials and Regenerative Medicine, Weifang, 261053, People’s Republic of China; 2College of Pharmacy, Weifang Medical University, Weifang, 261053, People’s Republic of China; 3Department of Dermatology, Affiliated Hospital of Weifang Medical University, Weifang, 261031, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guoyan Liu; Linlin Hu Tel/Fax +86 15715369896Email wfliuguoyan@126.com; hull@wfmc.edu.cnPurpose: Malignant melanoma is one of the most devastating types of cancer with rapid relapse and low survival rate. Novel strategies for melanoma treatment are currently needed to enhance therapeutic efficiency for this disease. In this study, we fabricated a multifunctional drug delivery system that incorporates dacarbazine (DTIC) and indocyanine green (ICG) into manganese-doped mesoporous silica nanoparticles (MSN(Mn)) coupled with magnetic resonance imaging (MRI) and photothermal imaging (PI), for achieving the superior antitumor effect of combined chemo-photothermal therapy.Materials and Methods: MSN(Mn) were characterized in terms of size and structural properties, and drug loading and release efficiency MSN(Mn)-ICG/DTIC were analyzed by UV spectra. Photothermal imaging effect and MR imaging effect of MSN(Mn)-ICG/DTIC were detected by thermal imaging system and 3.0 T MRI scanner, respectively. Then, the combined chemo-phototherapy was verified in vitro and in vivo by morphological evaluation, ultrasonic and pathological evaluation.Results: The as-synthesized MSN(Mn) were characterized as mesoporous spherical nanoparticles with 125.57± 5.96 nm. MSN(Mn)-ICG/DTIC have the function of drug loading-release which loading ratio of ICG and DTIC could reach to 34.25± 2.20% and 50.00± 3.24%, and 32.68± 2.10% of DTIC was released, respectively. Manganese doping content could reach up to 65.09± 2.55 wt%, providing excellent imaging capability in vivo which the corresponding relaxation efficiency was 14.33 mM− 1s− 1. And outstanding photothermal heating ability and stability highlighted the potential biomedical applicability of MSN(Mn)-ICG/DTIC to kill cancer cells. Experiments by A375 melanoma cells and tumor-bearing mice demonstrated that the compound MSN(Mn)-ICG/DTIC have excellent biocompatibility and our combined therapy platform delivered a superior antitumor effect compared to standalone treatment in vivo and in vitro.Conclusion: Our findings demonstrate that composite MSN(Mn)-ICG/DTIC could serve as a multifunctional platform to achieve a highly effective chemo-photothermal combined therapy for melanoma treatment.Keywords: Mn-doped mesoporous silica, drug delivery, magnetic resonance imaging, combination therapy